Specifike jezikovnih izbir novinarjev v radijskih novinarskih dvogovornih žanrih - Verovnik, Tina (Teorija in praksa, 2009)
The article presents the theoretical background and findings of the authorćs research examining whether journalistsć linguistic choices in radio interviews were primarily genre-driven or market-driven, or guided by another reason. The results of the analysis show that the predominant influences governing the linguistic choices were genre, audience and (at least to some extent) the radio programme type. With respect to these influences, two major stylistic types were detected: one that shows characteristics similar to those of standard spoken language and cultivated sociolects; and another that includes linguistic markers, typical of the sociolects of the audience(s) of a certain radio programme type.
Keywords: Novinarji; Radio; Novinarske zvrsti; Journalists; Intervju; Journalistic genre; Stilistika; Interview; Stylistics; mass media; množični mediji; radijski govor; Slovene; slovenščina; raziskave